Flourishing-Life-Of-Wish Virtual Reality Relaxation Therapy (FLOW-VRT-Relaxation) outperforms traditional relaxation therapy in palliative care: results from a randomized controlled trial - Woo, Olive K. L.; Lee, Antoinette M.; Ng, Royce; Eckhoff, Daniel; Lo, Raymond; Cassinelli, Alvaro (Frontiers in Virtual Reality, 2024)
As the global population continues to age, the demand for palliative care is progressively increasing. This growing trend highlights the pressing need for groundbreaking interventions that can effectively manage palliative symptoms and improve the quality of end-of-life care. We present a brief, structured, personalized, and innovative psychological intervention named Flourishing-Life-Of-Wish Virtual Reality Therapy (FLOW-VRT), which capitalizes on the distinctiveness of virtual reality (VR) as an advanced technology for symptom management. FLOW-VRT is theoretically based on self-determination theory, stress coping theory, flow theory, and attention restoration theory. With a special focus on relaxation, “FLOW-VRT-Relaxation” is designed to enhance end-of-life coping through personalized VR relaxation. As most studies on the use of VR in palliative care have been feasibility or pilot studies with small sample sizes, there is a need for a randomized controlled trial with sufficient statistical power. Using a randomized controlled trial (n =128), we tested the efficacy of FLOW-VRT-Relaxation by comparing it to traditional relaxation practice in palliative care. Our results show that following a FLOW-VRT-Relaxation session, the symptoms of distress that patients in palliative care have to endure significantly reduce, whether physical or emotional in nature. The current findings give promising results regarding the therapeutic potential of using FLOW-VRT-Relaxation as a cost-effective, scalable, and personalized VR relaxation for patients in palliative care.